Sebuah Efektivitas Teknik dan Efisiensi Metode Hafalan pada Bagian Chaconne serta integrasinya terhadap seluruh bagian - Betania, Nonni (Prodi D4 Penyajian Musik FSP ISI Yogyakarta, 2018)
Partita number 2 in D minor by Johann Sebastian Bach for solo violin becomesone of the most important works in the world of music especially violin playersaround the world. The most famous part is Chaconne because it has variedtechniques, long duration and also unique because it has a different form of variationfrom the previous sections. To be able to play this repertoire, the author made severalsteps that include technique formulations, applying memorizing methods, evaluationand discussion, and concert trials. The technique problem-solving process that hasbeen formulated is done by recapitulation method of motif especially in Chaconnesection because this section covers the whole repertoire technique. The authorsclassify the process of training into 2, named the left and right hand that includesscale, arpeggio, double stop, and vibrato for the left hand, and legatissimo, legato,detache, staccato, spiccato, multi-stopping, legato staccato, and also crossing bow forhand right. Memory methods applied by the author include melody identification,motive grouping, harmony identification, and run trough process. The process ofmemorization is also supported by listening to the soloist’s record of violin playingthis repertoire. The integration of the Chaconne section with previous sections ie allsections written in the D minor scales such as the Partita feature in general, containsthe accumulation of techniques from the previous sections, as well as represents theclimax of taste and emotion throughout the repertoire so that it can be concluded thatwhen the author is able to master technique in Chaconne means able to master alltechniques in Partita number 2. The factors supporting the success of this recital isphysical endurance and preparation of instruments. The result of this research isauthor succeeds in mastering the double stop techniques and variations of bowing,the accuracy of positioning and dynamics, producing varied frictional characters, andproducing vibrato on single stop or double stop and play it by memorizing in recital.